Risk of incident colorectal cancer and death after colonoscopy: a population-based study in Utah - Samadder, Niloy Jewel; Curtin, Karen; Pappas, Lisa; Boucher, Ken; Mineau, Geraldine P.; Smith, Ken; Fraser, Alison; Wan, Yuan; Provenzale, Dawn; Kinney, Anita Y.; Ulrich, Cornelia; Burt, Randall W. (Clinical gastroenterology and hepatology, 2016)
Colonoscopy is widely recommended for colorectal (CRC) screening in the United States, but evidence of effectiveness is limited. We examined whether exposure to colonoscopy decreases the odds of incident CRC and death from CRC in Utah.
Available online 4 September 2015
Gesehen am 08.05.2020